Radiation-induced premature ovarian failure: focus on the role of ovarian inflammatory signaling pathways - Doaa H. Mohamed; Eman M. Mantawy; Riham S. Said; Dina H. Kassem; Amany M. Gad; Ebtehal El-Demerdash (Archives of Pharmaceutical Sciences Ain Shams University)
Radiation therapy, an effective treatment modality for many types of cancer, often carries a heavy cost for young women. In particular, those undergoing pelvic radiotherapy mostly experience sudden menopausal symptoms and premature ovarian failure (POF) impacting their reproductive health and overall quality of life. Upon radiation, excessive reactive oxygen species (ROS) are produced causing a state of oxidative stress to tissues. Following this, DNA is damaged augmenting subsequent inflammatory responses and further tissue damage. Mild inflammation is essential for the development and release of oocytes; however, Pro-longed inflammation is associated with poor quality oocytes and sometimes complete dysfunction of the ovaries, as excessively produced, pro-inflammatory cytokines like Tumor necrosis factor-alpha (TNF-α) and interleukins lead to compromised ovary functionality. This work aims at considering the radiation induced POF as an inflammatory process. It also covers key molecular pathways involved in this response like nuclear factor kappa-B (NFκ-b), Transforming growth factor-β (TGF-β), Mitogen-activated protein kinase (MAPK), Sirtuin 1 (SIRT1), Poly [ADP-ribose] polymerase 1 and insulin like growth factor-1 (IGF-1) in regulating inflammation. Eventually, understanding these interrelated pathways can provide researchers with valuable molecular targets that can be used to develop new protective agents for radiation induced POF and thus improve the quality of life for these patients.